Intraperitoneal paclitaxel for patients with primary malignant peritoneal mesothelioma: a phase I/II dose escalation and safety study—INTERACT MESO - Job P van Kooten; Jacobus W A Burger; Cornelis Verhoef; Joachim G J V Aerts; Eva V E Madsen; Alexandra R M Brandt-Kerkhof; Stijn L W Koolen; Ron H J Mathijssen; Michelle V Dietz; Niels A D Guchelaar (BMJ Open)
Introduction Malignant peritoneal mesothelioma (MPM) is a rare, aggressive tumour arising primarily from the peritoneum. The only potentially curative treatment is cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC). However, the majority of patients are not eligible to undergo this treatment. The benefit of systemic treatment for these patients is limited at the cost of considerable morbidity. Hence, there is a need for appropriate palliative treatment options for patients with MPM. As MPM rarely disseminates outside the abdominal cavity, these patients might benefit from local treatment. A higher, more effective dose of chemotherapy can directly be delivered at the site of the disease. Systemic uptake will be limited, likely resulting in less toxicity. The aim of the INTERACT MESO trial is to determine the maximum tolerable dose of intraperitoneal paclitaxel monotherapy in patients with MPM. Secondary endpoints are to assess safety and toxicity, feasibility and the pharmacokinetic profile of this treatment.Methods and analysis The INTERACT MESO trial is a prospective, open-label, single-centre, phase I study with a classic three-plus-three dose escalation design. The study population consists of adult patients with primary MPM, without extra-abdominal disease, who are not eligible to undergo CRS-HIPEC. According to standard of care work-up for CRS-HIPEC, patients will undergo diagnostic laparoscopy to determine the feasibility of CRS-HIPEC. In case CRS-HIPEC is not considered feasible, a peritoneal port-a-cath (PAC) system will be placed. Through this PAC, 8–16 weekly cycles of intraperitoneal chemotherapy will be administered.Ethics and dissemination The Central Committee on Research Involving Human Subjects (CCMO, The Hague, The Netherlands) and the Medical Research Ethics Committee (METC, Rotterdam, The Netherlands) have granted permission to carry out this study protocol. The results of this trial will be submitted for publication in a peer-reviewed scientific journal.Trial registration number NL9718. EudraCT: 2021-003637-11.